Trends in Distribution and Case Fatality Rates of Cardiovascular Disease in West Nusa Tenggara General Hospital for 2014-2022 - Yusra Pintaningrum; Romi Ermawan; Yanna Indrayana; AASG Mas Meiswaryasti Putra; M. Syahrial Luthfi; Ketut Angga Aditya Putra Pramana; Ni Gusti Ayu Made Sintya Dwi Cahyani (Postgraduate, University of Mataram, 2025)
Background: Cardiovascular disease (CVD) is the leading cause of death, which affects 17.9 million people every year. This study aimed to determine trends in CVD distribution and case fatality rate (CFR) at the West Nusa Tenggara Province General Hospital, the major referral hospital in West Nusa Tenggara Province of Indonesia Methods: This study was descriptive with a retrospective approach using medical records of patients with CVD at the West Nusa Tenggara General Hospital from January 2014 to December 2022. Consecutive sampling was performed. Data based on diagnosis, patient age, gender, and case fatality rates were analyzed descriptively and expressed in frequency and percentage distribution. Results: Of the 11,742 patients included, more than half of the patients (58.92%) were male. In this study, the most common CVD was ischemic heart disease (IHD) (44.23%, n=5,194), followed by patients with hypertension (24.55%, n=2,883), and heart failure (19.30%, n=2,265) which were dominated by males, 68.34%, 57.25%, and 50.53%, respectively. Females were lower in those CVD due to estrogen hormone which has role as cardio protector that maintains the elasticity of blood vessels and prevents atherosclerosis. Meanwhile, mitral valve disease is the fourth most common CVD, approximately 6.69%, followed by atrial fibrillation or atrial flutter at 5.97%, which were dominated by females, 57.78% and 54.17%, respectively. Our data showed that the highest CFR was in patients with atrial fibrillation or atrial flutter, which was 17.5% in 2022. Conclusion. IHD is the most commonly found in the majority of patients with CVD. The highest case fatality rate is in atrial fibrillation or atrial flutter. CVD prevalence, or CFR, is essential to focus on treatment and prevention strategies.